Mengenal Pembelajaran Baca Tulis Alqur’an - Ayu Puspita Ningrum; Nur Aini Dewi; Isna Apriyanti; Roswita Rahmadhani Tambunan (UIN Sumatera Utara Medan, 2020)
This article aims to discuss the Basically Reading the Qur'an. This study uses the literature review method by critically tracing various sources of references to obtain reliable, intact data. The results of this study state that the Read the Qur’an is a lesson that learns how to read and write the Qur’an in accordance with the rules that are good and right. In studying the Qur’an it is necessary to understand the reading and writing of the Qur’an, because understanding reading and writing the Qur’an becomes an important requirement that must be mastered in studying and understanding the meaning of the verses of the Qur’an.